Biofilm formation on titanium alloy and anatase-Bactercline® coated titanium healing screws: an in vivo human study - Antonio Scarano; Domenico Tripodi; Francesco Carinci; Raffaele Piccolomini; Simonetta D'Ercole (Ariesdue, 2013)
Aim Bacterial adherence to implants is considered to be an important event in the pathogenesis of bacterial infections. In fact, this infection process is a first stage of peri-implant mucositis and peri-implantitis, and a positive correlation has been found between oral hygiene and marginal bone loss around implants in the edentulous mandible. Surface properties of transgingival implant components are important determinants in bacterial adhesion. The purpose of this study was to characterize the biofilm formation, in vivo, on healing screws made of titanium alloy or coated with a combination of anatase and Bactercline® product. Materials and methods Twenty-five patients, between 21- 37 years, in excellent systemic health, participated in this study. In each of the 25 participants, one anatase-Bactercline® coated healing screw (Test) and one titanium alloy (TI6Al4V) healing screw (Control) were adapted to two different implants. Quantitative and qualitative biofilm formation on healing abutments was analyzed by culture method.Results Bacterial adherence to the two different healing screws used in this study were compared. Statistically significant differences were found between the Control and the Test group for both aerobic and anaerobic bacterial counts (p<0,05). The microflora consisted both of Gram-positive and Gram-negative bacteria, and displayed a high variability. The anaerobic S. intermedius, potentially "pathogenic", was isolated only from the Control group. Both healing screws harbored primarily Gram-positive rods as Actinomyces spp, A. naeslundii, A. viscosus and the Gram-negative rods (Fusobacterium spp, Prevotella spp, Capnocythophaga spp) were mostly found on the Control healing screws.Conclusion Anatase-Bactercline® coated healing screws reduce the number of initially adhering bacteria, formed mainly of Gram-positive microorgnisms, while, on the contrary, the microflora covering the titanium alloy healing screws was, for the most part, Gram-negative.